COMPARATIVE ANALYSIS OF THE COMPUTER VISION SYNDROME BETWEEN THE DEVELOPED EU COUNTRIES AND REPUBLIC OF SERBIA - VIDUKA, Dejan; BAŠIĆ, Ana; BALABAN, Petra (Journal of process management and new technologies, 2024)
It is hard to envisage any business activity nowadays without the use of computers. The users who in their work utilize computers or some other displays for viewing electronic contents are exposed to the computer vision syndrome effects. This paper defines the computer vision syndrome and explains occurrences of the syndrome, setting out also its consequences. Analysis has been made of the viewpoints of users from the developed EU countries regarding the computer vision syndrome. Comparison has been made of the obtained data with the data showing viewpoints of the users in the Republic of Serbia. The aim of this analysis is to form a comprehensive picture of the computer vision syndrome issues. At the end of the paper, solutions are depicted for reducing the consequences and preventing the computer vision syndrome occurrences.
Keywords: computer display; eye aids; computer vision syndrome – CVS; engineering work; eye morphology